2015
DOI: 10.1111/jdi.12387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics in patients with type 2 diabetes among whom different antihyperglycemic agents were prescribed as monotherapy or combination therapy by diabetes specialists

Abstract: Aims/IntroductionWe compared clinical characteristics in patients with type 2 diabetes for whom different antihyperglycemic agents were prescribed as monotherapy or combination therapy by diabetes specialists in Japan.Materials and MethodsPrescription data for 2005, 2008 and 2011 from diabetes specialists' patient registries identified variables related to prescription of different antihyperglycemic agents.ResultsA total of 33,251 prescriptions in 2005, 25,119 in 2008 and 20,631 in 2011 were analyzed. Prescrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The progressive nature of T2DM associated with the loss of β-cell function results in deterioration of glycemic control, which entails treatment intensification with a combination of oral anti-diabetes drugs and glucagon-like peptide-1 receptor agonists (OADGs), and eventually insulin treatment [ 5 ]. The use of insulin has become quite prevalent in the Japanese population, with ~ 30% of patients receiving insulin either as a monotherapy or in combination with other OADGs [ 5 8 ]. Despite the availability of several OADGs and the increased use of insulin, most patients still fail to achieve glycemic control goals, which might possibly be due to increased risk of hypoglycemia, weight gain, and insufficient social support for the use of insulin, especially for patients with dementia or fear of injectables [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progressive nature of T2DM associated with the loss of β-cell function results in deterioration of glycemic control, which entails treatment intensification with a combination of oral anti-diabetes drugs and glucagon-like peptide-1 receptor agonists (OADGs), and eventually insulin treatment [ 5 ]. The use of insulin has become quite prevalent in the Japanese population, with ~ 30% of patients receiving insulin either as a monotherapy or in combination with other OADGs [ 5 8 ]. Despite the availability of several OADGs and the increased use of insulin, most patients still fail to achieve glycemic control goals, which might possibly be due to increased risk of hypoglycemia, weight gain, and insufficient social support for the use of insulin, especially for patients with dementia or fear of injectables [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of insulin has become quite prevalent in the Japanese population, with ~ 30% of patients receiving insulin either as a monotherapy or in combination with other OADGs [ 5 8 ]. Despite the availability of several OADGs and the increased use of insulin, most patients still fail to achieve glycemic control goals, which might possibly be due to increased risk of hypoglycemia, weight gain, and insufficient social support for the use of insulin, especially for patients with dementia or fear of injectables [ 8 , 9 ]. Hence, improvement in glycemic control without increasing the risk of hypoglycemia and weight gain is required when using OADGs in combination with insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale cohort studies in T2DM, such as the Japan Diabetes Complication and its Prevention prospective [ 6 , 9 ] and the Diabetes Clinical Data Management Study Group [ 5 , 10 ] studies in Japan, are often conducted at hospitals or clinics that specialize in diabetes. This is consistent with how diabetes studies are conducted overseas, including the landmark UK Prospective Diabetes study [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] The first drug of choice has dramatically changed in Japan, since several new drugs, as represented by dipeptidyl peptidase-4 inhibitors (DPP-4I), have been developed during the last decade. [ 7 9 ] In fact, a recent study revealed that the top three initially prescribed hypoglycemic agents in Japan were DPP-4I, biguanides, and sulfonylureas in that order. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…The Japan Diabetes Clinical Data Management Study Group (JDDM) is one of the largest cohorts of Japanese diabetes specialists consisting of more than 120 leading clinical diabetologists in 98 facilities and has provided information on characteristics of patients with T2DM as well as hypoglycemic prescriptions in Japan. [ 7 , 8 , 10 , 11 ] Therefore, using JDDM data we sought to determine the factors that influence the choice of each of 3 hypoglycemic agents prescribed as initial monotherapy by specialists as well as the patients’ factors that influenced the continuation or discontinuation of the drug or the addition of another drug over a 1-year period. Such information would be helpful in guiding the treatment of patients with T2DM by diabetes specialists and physicians in general practice in clinical settings.…”
Section: Introductionmentioning
confidence: 99%